2018
DOI: 10.1016/j.chemgeo.2018.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium isotopic fractionation between aqueous Zn and minerals from first-principles calculations

Abstract: Theoretical mineral-solution equilibrium isotopic fractionation can contribute to the interpretation of Zn isotopic compositions. In this study, we investigate equilibrium isotopic fractionation properties of hexaaquo zinc complex, a major Zn aqueous species, using first-principles molecular dynamics (FPMD) based on density functional theory (DFT). Pentaaquo and tetraaquo zinc complexes, which can be relevant for specific mechanisms such as adsorption on mineral surfaces, are also considered. This approach tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 46 publications
4
18
0
Order By: Relevance
“…The bond strength can be measured by the force constant (Ducher et al, 2018;Li et al, 2019b;Mavromatis et al, 2020), as revealed by the linear relationship between the 3 lnβ and the force constant <F> of Ba (Fig. 3b).…”
Section: Reduced Partition Function Ratios Of 137 Ba/ 134 Bamentioning
confidence: 99%
See 2 more Smart Citations
“…The bond strength can be measured by the force constant (Ducher et al, 2018;Li et al, 2019b;Mavromatis et al, 2020), as revealed by the linear relationship between the 3 lnβ and the force constant <F> of Ba (Fig. 3b).…”
Section: Reduced Partition Function Ratios Of 137 Ba/ 134 Bamentioning
confidence: 99%
“…As such, estimating the β factors of aqueous ions such as Ba 2+ , Mg 2+ , and Zn 2+ is more complicated and requires higher computational costs than calculating mineral β factors (Kowalski et al, 2013;Ducher et al, 2018;. In order to simplify the theoretical calculations, some previous studies used the crystal structures of hydroxide polyhydrates to model the structures of aqueous ions (Schauble, 2011;Li et al, 2019b;Mavromatis et al, 2020 .…”
Section: Can Aqueous Ions Be Modeled By Hydroxide Polyhydrates For Estimating β Factors?mentioning
confidence: 99%
See 1 more Smart Citation
“…In natural waters and hydrothermal solutions, Zn occurs as the free ion, i.e. Zn 2+ , solvated by water molecules (Ducher et al, 2018), as Zn complexed to organic ligands or humic acids (Jouvin et al, 2009Mar ovi et al, 2017, and complexed with inorganic ligands such as chloride. Experimental and theoretical investigations on Zn complexation by organic ligands (Ban et al, 2002;Black et al, 2011;Jouvin et al, 2009, Fuji andAlbarède, 2012;Mar ovi et al, 2017) has shown that such complexes favor in general heavy Zn isotopes controlled by the affinity constant.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2014) suggested that heavier Zn isotope favors the fluid phase during high temperature water-rock reactions. Fujii et al (2011Fujii et al ( , 2014 and Ducher et al (2016Ducher et al ( , 2018 calculated the fractionation factors of Zn compounds in aqueous fluids. However, the causes for large variations in Zn isotopic compositions of fumaroles from volcanic studies (Toutain et al, 2008;Chiaradia et al, 2018) and sphalerite in hydrothermal deposits (Mathur and Wang, 2019) are still controversial.…”
Section: Introductionmentioning
confidence: 99%